A complete procedure for predicting and improving the performance of HAWTs - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Sittig, Florian; Delgado, Antonio (Journal of Physics: Conference Series, 2014)
A complete procedure for predicting and improving the performance of the horizontal axis wind turbine (HAWT) has been developed. The first process is predicting the power extracted by the turbine and the derived rotor torque, which should be identical to that of the drive unit. The BEM method and a developed post-stall treatment for resolving stall-regulated HAWT is incorporated in the prediction. For that, a modified stall-regulated prediction model, which can predict the HAWT performance over the operating range of oncoming wind velocity, is derived from existing models. The model involves radius and chord, which has made it more general in applications for predicting the performance of different scales and rotor shapes of HAWTs. The second process is modifying the rotor shape by an optimization process, which can be applied to any existing HAWT, to improve its performance. A gradient- based optimization is used for adjusting the chord and twist angle distribution of the rotor blade to increase the extraction of the power while keeping the drive torque constant, thus the same drive unit can be kept. The final process is testing the modified turbine to predict its enhanced performance. The procedure is applied to NREL phase-VI 10kW as a baseline turbine. The study has proven the applicability of the developed model in predicting the performance of the baseline as well as the optimized turbine. In addition, the optimization method has shown that the power coefficient can be increased while keeping same design rotational speed. © Published under licence by IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2014.tech.ITC.stmmec.acompl
Keywords: BEM; Horizontal Axis Wind Turbine; Optimization; performance predicting control strategies

A design and optimization method for matching the torque of the wind turbines - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Weber, Horst; Delgado, Antonio (Journal of Renewable and Sustainable Energy, 2015)
An aerodynamic shape optimization method for a horizontal axis wind turbine is developed and verified through experimentation with a laboratory-scale wind turbine. Our method is based on matching the rotor's and the coupled generator's torque. Prior to shape optimization, an initial rotor design is established with a hybrid use of Schmitz and blade element momentum theories. The experimental verification of the developed method is conducted with a small-scale wind turbine; thus, the operating Reynolds number is one order of magnitude lower than large-scale wind turbines. Therefore, a high-lift low-Re airfoil, namely, SG6043, is selected for the blade along the whole span. The shape is optimized by determining the optimum chord and cumulative pitch angle distributions by manipulating the tapering and twisting of the blade. The objective of the optimization is to maximize the turbine's power coefficient Cp, while maintaining the torque equal to that of the generator. The generator's characteristics are found through experimentations which are conducted apart from the wind tunnel experiments. During the optimization process, the local aerodynamic forces on the blade are calculated by interfacing the optimization program with XFOIL; thus, the torque and power can be calculated for the rotor at each iteration step. The optimized turbine performance is evaluated under a design and off-design operating condition. The performance verification experiments are carried out in the wind tunnel with a specially designed setup. A comparison of the measured and computed performance shows good agreement.
UnivIS-Import:2015-07-08:Pub.2015.tech.ITC.stmmec.adesig

Aerodynamic optimization of HandiHaler and Respimat: the roles of computational fluid dynamics and flow visualization - Wachtel, Herbert; Ertunc, Özgür; Köksoy, Cagatay; Delgado, Antonio (Respiratory Drug Delivery 2008 (2008), 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.aerody_1

Alteration of power spectra of velocity fluctuations in a turbulent round jet flow - Köksoy, Cagatay; Ertunc, Özgür; Delgado, Antonio; Derlien, Hans (8 EFMC, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.altera

A method for the aerodynamic design of dry powder inhalers - Ertunc, Özgür; Köksoy, Cagatay; Wachtel, Herbert; Delgado, Antonio (International Journal of Pharmaceutics, 2011)
An inhaler design methodology was developed and then used to design a new dry powder inhaler (DPI) which aimed to fulfill two main performance requirements. The first requirement was that the patient should be able to completely empty the dry powder from the blister in which it is stored by inspiratory effort alone. The second requirement was that the flow resistance of the inhaler should be geared to optimum patient comfort. The emptying of a blister is a two-phase flow problem, whilst the adjustment of the flow resistance is an aerodynamic design problem. The core of the method comprised visualization of fluid and particle flow in upscaled prototypes operated in water. The prototypes and particles were upscaled so that dynamic similarity conditions were approximated as closely as possible. The initial step in the design method was to characterize different blister prototypes by measurements of their flow resistance and particle emptying performance. The blisters were then compared with regard to their aerodynamic performance and their ease of production. Following selection of candidate blisters, the other components such as needle, bypass and mouthpiece were dimensioned on the basis of node-loop operations and validation experiments. The final shape of the inhaler was achieved by experimental iteration. © 2011 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.ametho
Keywords: Design; DPI; Dry powder; Flow visualization; Fluid mechanics; Inhaler

Analyse des Strömungs- und Transitionsverhaltens freier synthetischer Jets mittels direkter numerischer Simulation und optischer Messverfahren - Glowienko, Robert; Derlien, Hans; Ertunc, Özgür; Delgado, Antonio (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)
UnivIS-Import:2018-09-11:Pub.2014.tech.ITC.stmmec.analys

An analytical model for droplet separation in vane separators and measurements of grade efficiency and pressure drop - Koopmann, Hans K.; Köksoy, Cagatay; Ertunc, Özgür; Lienhart, Hermann; Hedwig, Heinz-Jürgen; Delgado, Antonio (Nuclear Engineering and Design, 2014)
This study investigates the predictive power of analytical models for the droplet separation efficiency of vane separators and compares experimental results of two different vane separator geometries. The ability to predict the separation efficiency of vane separators simplifies their design process, especially when analytical research allows the identification of the most important physical and geometrical parameters and can quantify their contribution. In this paper, an extension of a classical analytical model for separation efficiency is proposed that accounts for the contributions provided by straight wall sections. The extension of the analytical model is benchmarked against experiments performed by Leber (2003) on a single stage straight vane separator. The model is in very reasonable agreement with the experimental values. Results from the analytical model are also compared with experiments performed on a vane separator of simplified geometry (VS-1). The experimental separation efficiencies, computed from the measured liquid mass balances, are significantly below the model predictions, which lie arbitrarily close to unity. This difference is attributed to re-entrainment through film detachment from the last stage of the vane separators. After adjustment for re-entrainment effects, by applying a cut-off filter to the outlet droplet size spectra, the experimental and theoretical outlet Sauter mean diameters show very good agreement. A novel vane separator geometry of patented design (VS-2) is also investigated, comparing experimental results with VS-1. Experimental separation efficiencies based on recorded mass flow balances are very similar for both geometries. However, based on an analysis of the outlet droplet size spectra, VS-2 outperforms VS-1. It is concluded that re-entrainment effects cloud the performance of VS-2 and that the perforations in the wall sections of VS-2 are not very effective. Pressure drop measurements performed on both geometries reveal that the pressure drop for VS-2 is higher than for VS-1 by a factor of almost two for gas velocities up to 10 m/s. © 2014 Elsevier B.V.
UnivIS-Import:2015-04-14:Pub.2014.tech.ITC.stmmec.ananal

A torque matched aerodynamic performance analysis method for the horizontal axis wind turbines - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Weber, Horst; Delgado, Antonio (Wind Energy, 2013)
An analysis method is developed to test the operational performance of a horizontal axis wind turbines. The rotor is constrained to the torque-speed characteristic of the coupled generator. Therefore, the operational conditions are realized by matching the torque generated by the turbine over a selected range of incoming wind velocity to that needed to rotate the generator. The backbone of the analysis method is a combination of Schmitz' and blade element momentum (BEM) theories. The torque matching is achieved by gradient-based optimization method, which finds correct wind speed at a given rotational speed of the rotor. The combination of Schmitz and BEM serves to exclude the BEM iterations for the calculation of interference factors. Instead, the relative angle is found iteratively along the span. The profile and tip losses, which are empirical, are included in the analysis. Hence, the torque at a given wind speed and rotational speed can be calculated by integrating semi-analytical equations along the blade span. The torque calculation method is computationally cheap and therefore allows many iterations needed during torque matching. The developed analysis method is verified experimentally by testing the output power and rotational speed of an existing wind turbine model in the wind tunnel. The generator's torque rotational speed characteristic is found by a separate experimental set-up. Comparison of experiments with the results of the analysis method shows a good agreement.
UnivIS-Import:2015-03-09:Pub.2014.tech.ITC.stmmec.atorqu
Keywords: BEM theory; Horizontal axis wind turbine; Optimization; Power coefficient and performance measurements; Schmitz' theory

Beobachtung des Stofftransports ausgewählter Fluide in überkritischem Kohlendioxid - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Delgado, Antonio (Proceedings der 18. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.beobac

Connection between full-lifetime and breakdown of puffs in transitional pipe flows - Nishi, Mina; Ertunc, Özgür; Delgado, Antonio (2010)

Cooling of LEDs by synthetic jets - Glowienko, Robert; Ertunc, Özgür; Delgado, Antonio (2010)
Because of their continuously increasing efficiency, light-emitting diodes find new application areas. They are currently employed in automotive lighting for daytime running lights and rear lamps, but their usage is expanding to the main functions as high and low beam at the present time. Since 2008, Audi R8 is equipped with the first full LED headlamp, the model Audi A8 will follow in April 2010.In comparison to traditional lighting, LEDs offer not only various advantages but also a major challenge: With increasing junction temperature, their luminous efficiency and life cycle decline and passing the maximum junction temperature will even lead to a total failure. As almost 85% of the electric input is transformed to heat, thermal management becomes a critical task to be accomplished for successful application of LEDs. Therefore, suitable cooling concepts are necessary to reach a high efficiency and a long life span of the LEDs and to secure the lighting function.This paper introduces the previous findings for a systematic usage of so-called synthetic jets as an alternative to cooling of LEDs with fans. First of all the present cooling concept which is using small fans will be described. Then the generation of synthetic jets and their characteristics will be explained by means of literature survey, illustrations and numerical simulations. Their technical realization and advantages will be discussed and finally the future perspective and secure employment of LEDs in automotive headlamps will be provided.

Development of an experimental setup for double rotor HAWT investigation - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Epple, Philipp; Körbel, Wolfgang; Delgado, Antonio (Proceedings of ASME Turbo Expo 2012, 2012)
An experimental set-up was designed and constructed to study the performance of single and double rotor Horizontal Axis Wind Turbines (HAWT) configurations. Different tip speed ratios (TSR) were tested under varying wind loadings. The experimental study was carried out in order to investigate the HAWT performance and thereby increase its aerodynamics efficiency. Another setup was built to measure the torque rotational speed characteristic of the generator. The double rotor configuration was chosen intentionally to study the efficiency improvements when the second downstream rotor extracts the kinetic energy dismissed by the upstream rotor. The study showed that the power coefficient can be indeed increased about 50 % with a double rotor HAW T configuration, and the power gained from a counter rotating rotor is higher than that of a co-rotating rotor owing to the effect of the wake of the upstream rotor. In addition, a theoretical analysis of wake effect of the upstream rotor on the downstream rotor including the effect of the distance between the two rotors on the total power coefficient was made and investigated experimentally in order to estimate the optimum distance between the two rotors. Copyright © 2012 by ASME.
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.develo_7

Direct measurement of lifetime of transitional structures in low reynolds number pipe flows - Nishi, Mina; Ertunc, Özgür; Delgado, Antonio (6th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2009, 2009)
The lifetime of transitional flow structures in low Reynolds number pipe flows, namely puffs, was directly measured by measuring pressure drop transients in the pipe, which occur due to the generation and existence of a single transitional flow structure in the pipe. Transitional structures were generated by disturbing the flow with an iris diaphragm, which blocked the fully developed laminar flow with a certain blockage ratio and duration. Simultaneous to pressure measurements, measurements of velocity were conducted at the exit of the pipe by a hot-wire anemometry. Pipes having lengths of 200, 300 and 566 pipe diameters were employed. Pressure measurements allowed the direct determination of the lifetime of a puff, only when it dissipates in the pipe. The velocity measurements allow to determine the structure of single puffs and used to evaluate the probability of puff occurrence (survival) at the end of the pipe. The investigations of lifetime exhibited three possible routes for the development and/or the dissipation of puffs with increasing Reynolds number: Up to Re ≈ 1880, the disturbed structures develop into puffs then dissipate. After that Reynolds number, some of the puffs started to sustain remarkably longer within the pipe and some of them reaches to the end of the pipe before they dissipate. Within a very narrow Re range around 1500, the life of transitional structures was observed to remain constant. The directly measured lifetime in the range 1600 ≤ Re ≤ 1880 revealed a divergence of lifetime at Re ≈ 2300. It is demonstrated that disturbance amplitude and duration do not influence the directly measured lifetime, whereas they influenced the probability of occurrence of the puffs at the exit of the pip
Keywords: Couette flow; Shear flow; transient growth

Evolution of transitional structures from puff to slug through multiple splitting in a pipe flow at low Reynolds number - Krauß, Jens; Ertunc, Özgür; Ostwald, Christina; Lienhart, Hermann; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
During laminar-to-turbulent transition in low Reynolds pipe flows, three main types of flow structures occur: traveling waves and the turbulent flow structures, namely puffs and slugs. In the present work, detailed experiments on the probability of occurrence and propagation speed of puffs, splitting puffs and slugs were conducted with the transition pipe-flow facility of LSTM-Erlangen. During the investigations, fully developed laminar pipe flow was triggered by an iris diaphragm with a pre-defined amplitude and lapse time. Different types of single and multiple puffs are classified and the probability of their occurrence as well as their propagation speed at the end of pipes with different lengths are evaluated.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.evolut_4

Experimental investigation of particle deagglomeration using turbulence - Köksoy, Cagatay; Ertunc, Özgür; Hüttner, Sebastian; Wachtel, Herbert; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The effect of turbulence on powder aerosol deagglomeration was investigated. Two impinging jets were used to generate turbulence. Lactose particles, whose fully dispersed fine particle fraction (FPF) - number percentage of the particles whose diameter smaller than 5 μm- is above 90 %, were applied as aerosol powder. The particle size distribution after the dispersion unit were measured by using phase Doppler anemometer (PDA) and turbulence level were quantified at the impingement point of two jets with laser Doppler anemometer. As the turbulence level increases turbulent time and length scales decrease, and the ratio of fine particle fraction (FPF) increases from 36% to 86%.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.experi_1

From passive to active pitch regulation of wind turbines: Optimization method with numerical validation - Al-Abadi, Ali Kedher Kashin; Kim, You Jin; Park, Jinyoung; Kang, Hyunjin; Ertunc, Özgür; Delgado, Antonio (ASME 2015 9th International Conference on Energy Sustainability, ES 2015, collocated with the ASME 2015 Power Conference, the ASME 2015 13th International Conference on Fuel Cell Science, Engineering and Technology, and the ASME 2015 Nuclear Forum, 2015)
UnivIS-Import:2018-09-06:Pub.2015.tech.ITC.stmmec.frompa_5

From passive to active pitch regulation of wind turbines: Optimization method with numerical validation - Al-Abadi, Ali Kedher Kashin; Kim, You Jin; Park, Jinyoung; Kang, Hyunjin; Ertunc, Özgür; Delgado, Antonio (ASME Proceedings, Wind Energy Systems and Technologies, 2015)
An optimization method that changes the control strategy of the Horizontal Axis Wind Turbine (HAWT) from passive- to activepitch has been developed. The method aims to keep the rated power constant by adjusting the blade pitch angle while matching the rotor and the drive torques. The method is applied to an optimized wind turbine model. Further, numerical simulations were performed to validate the developed method and for further investigations of the flow behavior over the blades.
UnivIS-Import:2016-02-10:Pub.2015.tech.ITC.stmmec.frompa
Keywords: Cell engineering; Chemical analysis; Cooling systems; Electric power transmission networks; Numerical methods; Smart power grids; Solar power generation; Sustainable development; Wind power; Control strategies; Drive torque; Wind turbines

High-speed visualization of acoustically excited cavitation bubbles in a cluster near a rigid boundary - Vaidya, Haresh Anant; Ertunc, Özgür; Lichtenegger, Thomas; Hachmann, Johannes; Delgado, Antonio; Skupin, Andreas (Journal of Visualization, 2015)
Abstract: In the present work, high-speed visualizations at one million frames/s have been used to study the oscillation characteristics of acoustic cavitation bubbles. The bubbles are generated by acoustic cavitation using an ultrasound transducer with an excitation frequency of 75 kHz near a rigid surface and the medium used is deionized water. The cavitation bubbles tend to collect in clusters near solid boundaries, where they are visualized using a high-speed camera. The collective oscillations give rise to many interesting phenomena like bubble collapse, coalescence, fragmentation and bubble translation. The image sequences provided here contribute to the better understanding of the entire lifecycle of acoustic cavitation bubbles.
UnivIS-Import:2015-04-02:Pub.2015.tech.ITC.stmmec.highsp
Keywords: Acoustic cavitation; Bubble cluster; Bubble dynamics; High-speed visualizations; Ultrasound

High speed visualization of acoustic cavitation bubble dynamics near a rigid surface - Vaidya, Haresh Anant; Ertunc, Özgür; Skupin, Andreas; Delgado, Antonio (Proceedings der 21. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.highsp

Influence of turbulence on the performance of a laboratory scale HAWT - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Seok, Julie; Härtl, Michael; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.ITC.stmmec.influe

LDA measurements of Reynolds stresses in a swirling turbulent pipe flow - Genc, Balkan; Ertunc, Özgür; Jovanovic, Jovan; Delgado, Antonio (Advances in Turbulence XII - Proceedings of the 12th EUROMECH European Turbulence Conference, 2009)
UnivIS-Import:2017-12-18:Pub.2009.tech.ITC.stmmec.ldamea_2

LDA Messungen von Rohrströmungen mit Drall für einen breiten Bereich von Drallzahlen - Genc, Balkan; Ertunc, Özgür; Jovanovic, Jovan; Delgado, Antonio (Proceedings der 17. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik, 2009)
UnivIS-Import:2017-12-18:Pub.2009.tech.ITC.stmmec.ldames

Mass transfer of organic substances in supercritical carbon dioxide - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Neukam, Johannes; Bielke, Thorsten; Delgado, Antonio; Nercissian, Vanusch; Berger, Andreas (Journal of Physics : Conference Series, 2011)
In this work special attention is paid on the direct visualization of the diffusion process of oil droplets in supercritical carbon dioxide as well as better characterization of the process by quantitatively evaluating the important parameter - the diffusion coefficients obtained with a shearing interferometer. Experiments are also to be carried out under microgravity to improve the experiment condition where the influence of gravity-driven convection that usually dominates the transport process is minimized.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.masstr_3

Mass transfer of organic substances in supercritical carbon dioxide - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Delgado, Antonio; Nercissian, Vanusch; Berger, Andreas (Defect and Diffusion Forum, 2012)
In this work special attention is paid on the direct visualization of the diffusion process of oil droplets in supercritical carbon dioxide as well as a better characterization of the process by quantitative evaluation of the diffusion coefficients obtained with a shearing interferometer. Experiments are also to be carried out under microgravity in to improve the experiment condition where the influence of gravity-driven convection that usually dominates the transport process is minimized. © (2012) Trans Tech Publications.
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.masstr
Keywords: Diffusion coefficient; Microgravity; Shearing-interferometer; Supercritical carbon dioxide

Medizinverfahrenstechnik in der personalisierten Medizin: Hämodynamik von interkranialen Aneurysmen - Lopez Ramirez, Efrain; Delgado, Antonio; Benning, Rainer; Rauh, Cornelia; Münsch, Manuel; Ertunc, Özgür (Chemie Ingenieur Technik, 2010)
UnivIS-Import:2015-04-14:Pub.2010.tech.ITC.stmmec.medizi_6

Neuartige Methode für die aerodynamische Gestaltung von Pulverinhalatoren - Ertunc, Özgür; Wachtel, Herbert; Delgado, Antonio (Chemie Ingenieur Technik, 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.neuart

Novel, multi-objective optimization of pulsed electric field processing for liquid food treatment - Krauß, Jens; Ertunc, Özgür; Rauh, Cornelia; Delgado, Antonio (Innovative Food Processing Technologies: Advances in Multiphysics Simulation, 2011)
UnivIS-Import:2015-04-20:Pub.2011.tech.ITC.stmmec.novelm
Keywords: Best known effects of PEF-permeabilization of biological cells; Classification of optimization algorithms; Computational grid of colinear PEF chamber; Grid; structured; block structured or unstructured-complexity of geometry and capability of solver; Modeling and simulation of fields induced by PEF-in food capable of flowing; Models for PEF-induced inactivation-two different modeling approaches; managing PEF-induced inactivation; Novel; multi-objective optimization-of pulsed electric field processing in liquid food treatment; Numerical optimization of treatment chamber-and PEF process; Optimization of PEFs-method for treating biological matter; PEF chamber optimization and PEF process optimization-using genetic algorithm; MOGA II (multi-objective genetic algorithm) of modeFrontier

Numerical and experimental analysis of impinging synthetic jets for cooling a point-like heat source - Glowienko, Robert; Derlien, Hans; Ertunc, Özgür; Delgado, Antonio (Journal of Heat Transfer-Transactions of the Asme, 2018)
High power light emitting diodes (LEDs) being used for low and high beam in automotive lighting need active cooling of their heat sinks by radial or axial fans. But the moving elements of the fan cause abrasion, noise, and high energy consumption. Synthetic jets can replace conventional fans with their disadvantages and allow the directed cooling of LEDs. Therefore, in this paper, flow and heat transfer characteristics of impinging synthetic jets are investigated numerically and experimentally as an alternative to cooling LEDs with fans. It is shown that the impact plate brings forward the laminar-Turbulent transition of the jets temporally and spatially. The impact plate itself should not be positioned in the region of the free jet's transition height. Increasing the frequency of the synthetic jet has a greater influence on the heat transfer compared to an increase in amplitude. The maximum cooling performance is achieved for all jet configurations with moderate distances between the orifice and the impact plate. In this case, the jet reaches its highest mass flow and impulse and its lowest temperature.
UnivIS-Import:2018-09-11:Pub.2018.tech.ITC.stmmec.numeri
Keywords: Flow (Dynamics); Heat; Temperature; Heat transfer; Cooling; Jets; Turbulence; Vortices; Simulation; Impulse (Physics)

Numerical and experimental analysis of the ﬂow and transition of free synthetic jets - Delgado, Antonio; Glowienko, Robert; Derlien, Hans; Ertunc, Özgür (Fluid Dynamics Research, 2019)

Numerical simulation of non-thermal food preservation - Rauh, Cornelia; Krauß, Jens; Ertunc, Özgür; Delgado, Antonio (AIP Conference Proceedings, 2010)
Food preservation is an important process step in food technology regarding product safety and product quality. Novel preservation techniques are currently developed, that aim at improved sensory and nutritional value but comparable safety than in conventional thermal preservation techniques. These novel non-thermal food preservation techniques are based for example on high pressures up to one GPa or pulsed electric fields. in literature studies the high potential of high pressures (HP) and of pulsed electric fields (PEF) is shown due to their high retention of valuable food components as vitamins and flavour and selective inactivation of spoiling enzymes and microorganisms. for the design of preservation processes based on the non-thermal techniques it is crucial to predict the effect of high pressure and pulsed electric fields on the food components and on the spoiling enzymes and microorganisms locally and time-dependent in the treated product. Homogenous process conditions (especially of temperature fields in HP and PEF processing and of electric fields in PEF) are aimed at to avoid the need of over-processing and the connected quality loss and to minimize safety risks due to under-processing. the present contribution presents numerical simulations of thermofluiddynamical phenomena inside of high pressure autoclaves and pulsed electric field treatment chambers. in PEF processing additionally the electric fields are considered. Implementing kinetics of occurring (bio-) chemical reactions in the numerical simulations of the temperature, flow and electric fields enables the evaluation of the process homogeneity and efficiency connected to different process parameters of the preservation techniques. Suggestions to achieve safe and high quality products are concluded out of the numerical results. © 2010 American Institute of Physics.
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.numeri_29
Keywords: High Pressure Processing; Numerical Simulation; Process Design; Homogeneity; Pulsed Electric Field Processing

Numerical simulations of swirling pipe flows - decay of swirl and occurrence of vortex structures - Vaidya, Haresh Anant; Ertunc, Özgür; Genc, Balkan; Beyer, Florian; Köksoy, Cagatay; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The present work aims at better understanding of the physics underlying swirling flows in pipes by means of numerical simulations. Direct numerical simulations have been carried out by using two different inlet swirl conditions. In one case, rotating honeycomb is used as the means to generate swirl whereas in the other case a solid body rotation is provided at the inlet. The inlet swirl intensity is varied in order to scan the underlying physics. Reynolds number 1730 is selected so that the flow remains in laminar regime. The results are compared with those obtained from the experiments using a similar experimental set-up. It is shown that the increase in the inlet swirl intensity leads to a faster decay of swirl downstream of the pipe. Similarly certain specific vortex structures are observed in the radial velocity contours. These structures are thought to be analogous with those found in the Taylor-Couette flow between a stationary outer cylinder and inner rotating cone. The reported investigations reveal dependence of swirl decay on the inlet swirl intensity and occurrence of vortex structure

Numerical simulations of swirling pipe flows- decay of swirl and occurrence of vortex structures - Vaidya, Haresh Anant; Ertunc, Özgür; Genc, Balkan; Köksoy, Cagatay; Beyer, Florian; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The present work aims at better understanding of the physics underlying swirling flows in pipes by means of numerical simulations. Direct numerical simulations have been carried out by using two different inlet swirl conditions. In one case, rotating honeycomb is used as the means to generate swirl whereas in the other case a solid body rotation is provided at the inlet. The inlet swirl intensity is varied in order to scan the underlying physics. Reynolds number 1730 is selected so that the flow remains in laminar regime. The results are compared with those obtained from the experiments using a similar experimental set-up. It is shown that the increase in the inlet swirl intensity leads to a faster decay of swirl downstream of the pipe. Similarly certain specific vortex structures are observed in the radial velocity contours. These structures are thought to be analogous with those found in the Taylor-Couette flow between a stationary outer cylinder and inner rotating cone. The reported investigations reveal dependence of swirl decay on the inlet swirl intensity and occurrence of vortex structures.
UnivIS-Import:2015-04-14:Pub.2011.tech.ITC.stmmec.numeri_5

Numerische Validierung der experimentellen Daten eines optimierten HAWT - Numerical Validation of the Experimental Data of an Optimized HAWT - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Berger, Frederik; Seok, Julie; Delgado, Antonio (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)
In this work, an optimized HAWT has been analyzed numerically for validating its experi-mental data. The 3-D steady state CFD simulations have been performed in Star CCM+ with the RANS k-ω SST turbulence model. A single blade is modelled in a 120± fraction of a cy-lindrical domain, using periodic boundaries. Rotational effects are modelled by a frozen rotor approach. The design and off-design performance are investigated. The power coefficient was in good agreement with experimental data. Of special interest are the limitations of steady CFD investigations for the case of partially stalled conditions. It is shown that RANS investigations can provide good power indication despite boundary layer separation and re-versal flow. Additional information that can be obtained from simulation such as radial flow, detached boundary layer and flow circulation are presented as well
UnivIS-Import:2015-04-17:Pub.2014.tech.ITC.stmmec.numeri_37
Keywords: Numerical simulation; Optimization; HAWT

Partikuläre Systeme in der Mikrofluidik - Delgado, Antonio; Kowalczyk, Wojciech; Baars, Albert; Breuer, Michael; Ertunc, Özgür (Chemie Ingenieur Technik, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.ITC.stmmec.partik

Probability of occurrence of the turbulent flow structures in transitional pipe flows - Krauß, Jens; Ertunc, Özgür; Ostwald, Christina; Lienhart, Hermann; Delgado, Antonio (Notes on Numerical Fluid Mechanics and Multidisciplinary Design. New Results in Numerical and Experimental Fluid Mechanics VIII, 2013)
During laminar-to-turbulent transition in low Reynolds number (Re) pipe flows, two main types of turbulent flow structures occur: puff and slug. Puff structures can be initiated by inducing short-time, large amplitude localized disturbances in the pipe. They are equilibrium structures, i.e. they do not grow. Furthermore, they dissipate at random as they travel along the pipe. Therefore, they represent an incomplete relaminarization process. However, lifetimes of puffs diverge or attain very high values at some critical Re. At Reynolds numbers higher than this critical value, disturbances evolves from puff to slug through multiple splitting. In other words, the flow structures start to grow and fill the space. During this evolution, many types of structures occur. This evolution is associated with the onset of turbulence. In the present work, detailed experiments on the probability of occurrence and propagation speed of puffs, splitting puffs and slugs were conducted. During the investigations, fully developed laminar pipe flow was disturbed by an iris diaphragm with a pre-defined amplitude and duration. Different types structures, such as single puff, splitting puff and slugs, are classified and the probability of their occurrence at the end of pipes with different lengths are evaluated. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-20:Pub.2013.tech.ITC.stmmec.probab_8

Pulsating laminar fully developed channel and pipe flows - Haddad, Kais; Ertunc, Özgür; Mishra, Manoranjan; Delgado, Antonio (Physical Review E, 2010)
Analytical investigations are carried out on pulsating laminar incompressible fully developed channel and pipe flows. An analytical solution of the velocity profile for arbitrary time-periodic pulsations is derived by approximating the pulsating flow variables by a Fourier series. The explicit interdependence between pulsations of velocity, mass-flow rate, pressure gradient, and wall shear stress are shown by using the proper dimensionless parameters that govern the flow. Utilizing the analytical results, the scaling laws for dimensionless pulsation amplitudes of the velocity, mass-flow rate, pressure gradient, and wall shear stress are analyzed as functions of the dimensionless pulsation frequency. Special attention has been given to the scaling laws describing the flow reversal phenomenon occurring in pulsating flows, such as the condition for flow reversal, the dependency of the reversal duration, and the amplitude. It is shown that two reversal locations away from the wall can occur in pulsating flows in pipes and channels and the reversed amount of mass per period reaches a maximum at a certain dimensionless frequency for a given amplitude of mass-flow rate fluctuations. These analyses are numerically conducted for pipe and channel flows over a large frequency range in a comparative manner. © 2010 The American Physical Society.
UnivIS-Import:2015-04-14:Pub.2010.tech.ITC.stmmec.pulsat

Pulsating mass flow rate fully developed channel and pipe flows: A relative inspection - Haddad, Kais; Ertunc, Özgür; Mishra, Manoranjan; Delgado, Antonio (Physical Review E, 2010)
Analytical investigations are carried out on pulsating laminar incompressible fully developed channel and pipe flows. An analytical solution of the velocity profile for arbitrary time-periodic pulsations is derived by approximating the pulsating flow variables by a Fourier series. The explicit interdependence between pulsations of velocity, mass-flow rate, pressure gradient, and wall shear stress are shown by using the proper dimensionless parameters that govern the flow. Utilizing the analytical results, the scaling laws for dimensionless pulsation amplitudes of the velocity, mass-flow rate, pressure gradient, and wall shear stress are analyzed as functions of the dimensionless pulsation frequency. Special attention has been given to the scaling laws describing the flow reversal phenomenon occurring in pulsating flows, such as the condition for flow reversal, the dependency of the reversal duration, and the amplitude. It is shown that two reversal locations away from the wall can occur in pulsating flows in pipes and channels and the reversed amount of mass per period reaches a maximum at a certain dimensionless frequency for a given amplitude of mass-flow rate fluctuations. These analyses are numerically conducted for pipe and channel flows over a large frequency range in a comparative manne
UnivIS-Import:2018-09-05:Pub.2010.tech.ITC.stmmec.pulsat_4

Study of mass transfer in supercritical carbon dioxide (SCCO2) using optical methods - Delgado, Antonio; Benning, Rainer; Ertunc, Özgür; Hu, Miao; Nercissian, Vanusch; Berger, M. (Heat and Mass Transfer, 2017)

Study of mass transfer in supercritical carbon dioxide (SCCO2) using optical methods - Hu, Miao; Benning, Rainer; Delgado, Antonio; Ertunc, Özgür; Nercissian, Vanusch; Berger, M. (Heat and Mass Transfer, 2017)
The purpose of this work is to design and develop a type of experiment setup that would enable the direct observation of steady diffusion process in situ. Two different optical methods - shadowgraph and shearing interferometry - were used for the first time to visualise and quantitatively analyse the diffusion around a droplet of organic substance in supercritical carbon dioxide (SCCO2) as well as in its direct vicinity. We constructed and tested a cylindrical high-pressure chamber and an experiment system with a high speed camera. The solute/solvent combination of DL-α-tocopherol/SCCO2 was applied using shadowgraph. The diffusion coefficients at temperatures of 40o C, 50o C and 60o C and pressures between 75 bar and 90 bar were calculated based on the displacement of the droplet contour in the captured images. The shearing interferometry with a Wollaston-prism was then applied not only for the combination of DL-α-tocopherol/SCCO2, but also for other substances in SCCO2, for example for a type of rose oil and lubricant oil as well as for acetone, benzene, toluene and naphthalene. The changes of the refractive index gradient were directly measured and evaluated with the interferograms; afterwards changes of the density gradients and the diffusion coefficients were determined. We propose then a multivariate regression model to capture the relationship between the diffusion coefficient, the pressure and the temperature. To minimize the influence of gravity-driven convections in the solvent during diffusion, the experiments were also carried out under microgravity condition, i.e. in two parabolic flight campaign
UnivIS-Import:2018-02-22:Pub.2017.tech.ITC.stmmec.studyo

The evolution of transitional flow structures along a 3200 d pipe in the decay and growth regimes - Ertunc, Özgür; Krauß, Jens; Lienhart, Hermann; Schweiger, H.; Weber, Horst; Delgado, Antonio (ETC 2013 - 14th European Turbulence Conference, 2013)
The evolution of transitional flow structures along a 3200 D pipe in the decay and growth regimes are measured in a 3200 D structure tracking pipe flow facility. We report the statistics of the evolution for the probability of occurrence, characteristic lifetime, speed and length of the structures.
CRIS-Team Scopus Importer:2020-03-17

The penetration of acoustic cavitation bubbles into micrometer-scale cavities - Vaidya, Haresh Anant; Ertunc, Özgür; Lichtenegger, Thomas; Delgado, Antonio; Skupin, Andreas (Ultrasonics, 2015)
The penetration of acoustically induced cavitation bubbles in micrometer-scale cavities is investigated experimentally by means of high-speed photography and acoustic measurements. Micrometer-scale cavities of different dimensions (width = 40. μm, 80. μm, 10. mm and depth = 50. μm) are designed to replicate the cross section of microvias in a PCB. The aim here is to present a method for enhancing mass transfer due to the penetration of bubbles in such narrow geometries under the action of ultrasound. The micrometer-scale cavities are placed in a test-cell filled with water and subjected to an ultrasound excitation at 75. kHz. A cavitation bubble cluster is generated at the mouth of the cavity which acts as a continuous source of bubbles that penetrate into the cavity. The radial oscillation characteristics and translation of these bubbles are investigated in detail here. It is observed that the bubbles arrange themselves into streamer-like structures inside the cavity. Parameters such as bubble population and size distribution and their correlation with the phase of the incident ultrasound radiation are investigated in detail here. This provides a valuable insight into the dynamics of bubbles in narrow confined spaces. Mass transfer investigations show that fresh liquid can be continuously introduced in the cavities under the action of ultrasound. Our findings may have important consequences in optimizing the filling processes for microvias with high aspect ratios.
UnivIS-Import:2016-02-10:Pub.2015.tech.ITC.stmmec.thepen
Keywords: Acoustic cavitation; Bubble dynamics; Mass transfer; Microvias; Ultrasound

Torque-matched aerodynamic shape optimization of HAWT rotor - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Beyer, Florian; Delgado, Antonio (Journal of Physics : Conference Series, 2014)
Schmitz and Blade Element Momentum (BEM) theories are integrated to a gradient based optimization algorithm to optimize the blade shape of a horizontal axis wind turbine (HAWT). The Schmitz theory is used to generate an initial blade design. BEM theory is used to calculate the forces, torque and power extracted by the turbine. The airfoil shape (NREL S809) is kept the same, so that the shape optimization comprises only the chord and the pitch angle distribution. The gradient based optimization of the blade shape is constrained to the torque-rotational speed characteristic of the generator, which is going to be a part of the experimental set-up used to validate the results of the optimization study. Hence, the objective of the optimization is the maximization of the turbines power coefficient Cp while keeping the torque matched to that of the generator. The wind velocities and the rotational speeds are limited to those achievable in the wind tunnel and by the generator, respectively. After finding the optimum blade shape with the maximum Cp within the given range of parameters, the Cp of the turbine is evaluated at wind-speeds deviating from the optimum operating condition. For this purpose, a second optimization algorithm is used to find out the correct rotational speed for a given wind-speed, which is again constrained to the generator's torque rotational speed characteristic. The design and optimization procedures are later validated by high-fidelity numerical simulations. The agreement between the design and the numerical simulations is very satisfactory.
UnivIS-Import:2015-03-09:Pub.2014.tech.ITC.stmmec.torque
Keywords: Horizontal axis wind turbine; optimization; schmitz theory; bem; rotor blade design

Turbulence Impact on Wind Turbines: Experimental Investigations on a Wind Turbine Model - Al-Abadi, Ali Kedher Kashin; Kim, You-Jin; Ertunc, Özgür; Delgado, Antonio (Journal of Physics: Conference Series, 2016)
Experimental investigations have been conducted by exposing an efficient wind turbine model to different turbulence levels in a wind tunnel. Nearly isotropic turbulence is generated by using two static squared grids: fine and coarse one. In addition, the distance between the wind-turbine and the grid is adjusted. Hence, as the turbulence decays in the flow direction, the wind-turbine is exposed to turbulence with various energy and length scale content. The developments of turbulence scales in the flow direction at various Reynolds numbers and the grid mesh size are measured. Those measurements are conducted with hot-wire anemometry in the absence of the wind-turbine. Detailed measurements and analysis of the upstream and downstream velocities, turbulence intensity and spectrum distributions are done. Performance measurements are conducted with and without turbulence grids and the results are compared. Performance measurements are conducted with an experimental setup that allow measuring of torque, rotational speed from the electrical parameters. The study shows the higher the turbulence level, the higher the power coefficient. This is due to many reasons. First, is the interaction of turbulence scales with the blade surface boundary layer, which in turn delay the stall. Thus, suppressing the boundary layer and preventing it from separation and hence enhancing the aerodynamics characteristics of the blade. In addition, higher turbulence helps in damping the tip vortices. Thus, reduces the tip losses. Adding winglets to the blade tip will reduce the tip vortex. Further investigations of the near and far wake-surrounding intersection are performed to understand the energy exchange and the free stream entrainment that help in retrieving the velocit
UnivIS-Import:2018-02-22:Pub.2016.tech.ITC.stmmec.turbul

Untersuchung des Einflusses von Tensiden (oberflächenaktive Stoffe) auf die Dynamik der akustischen Kavitationsblasen in Wandnähe mithilfe von Hochgeschwindigkeitsaufnahmen - Vaidya, Haresh Anant; Ertunc, Özgür; Delgado, Antonio; Hachmann, Johannes; Lichtenegger, Thomas (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)
UnivIS-Import:2015-04-17:Pub.2014.tech.ITC.stmmec.unters

Untersuchungen zum Stofftransport ausgewählter Substanzen in überkritischem Kohlendioxid mittels Shearing-Intereferometrie - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Bielke, Thorsten; Delgado, Antonio; Neukam, Johannes; Nercissian, Vanusch; Berger, Andreas (Proceedings der 19. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.ITC.stmmec.unters

Visuelle Untersuchung turbulenter Jet-Strömung unter passiver Beeinflussung - Ertunc, Özgür; Derlien, Hans; Köksoy, Cagatay; Delgado, Antonio (Proceedings der 20. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.visuel